Cluster concept in policy planning documents: the cases of Latvia and Northern Cyprus - Garanti, Zanete; Zvirbule-Berzina, Andra; Yesilada, Tahir (Business: Theory and Practice, 2014)
Clusterbased entrepreneurship plays an important role in the economy of the 21st century. A regional cluster can be defined as a combination of 5 dimensions – single sector enterprises that cooperate and compete; supportive enterprises from a wide range of sectors; public and government institutions interested in economic development of the sector and region; other institutions, like research, education, finance and others and the fifth is regional dimension, which combines all four previously mentioned dimensions into one region. From the literature review standpoint, the findings of the authors show that cluster based entrepreneurship has an important role in stimulating the firm’s performance, competitiveness and innovation. Authors’ findings show that cluster concept is implemented in the EU policy planning documents at all levels, while in the country level cluster policy is not a single policy issue, but is implemented in industry, regional and other policy aspects. Example from Latvia shows that in recent years clusterbased entrepreneurship plays an important, if not central, role in policy planning documents, while evidence from Northern Cyprus shows that the importance attached to the concept of clusterbased economic development has not yet surfaced in the policy documents. Learning from experience of the EU and Latvia, the authors in cooperation with experts from University of Mediterranean Karpasia suggest policy makers in Northern Cyprus to implement clusterbased entrepreneur ship ideas in the policy documents using the bottomup approach. In this way cluster based entrepreneurship is implemented in policy planning documents in Northern Cyprus at region, industry and national level. This paper is the first attempt towards cluster concept recognition in Northern Cyprus and therefore the topic is opened for further discussions and recommendations. The target audience of this paper is policy makers in Northern Cyprus, as well as academicians and practitioners interested in clusterbased entrepreneurship development.